Identification of Low-Abundance Lipid Droplet Proteins in Seeds and Seedlings. Issue 3 (11th December 2019) - Kretzschmar, Franziska K.; Doner, Nathan M.; Krawczyk, Hannah E.; Scholz, Patricia; Schmitt, Kerstin; Valerius, Oliver; Braus, Gerhard H.; Mullen, Robert T.; Ischebeck, Till
Abstract : Several previously unknown low-abundant lipid droplet proteins are identified in Arabidopsis thaliana seeds and seedlings by quantitative proteomics combined with two cell biological approaches. Abstract: The developmental program of seed formation, germination, and early seedling growth requires not only tight regulation of cell division and metabolism, but also concerted control of the structure and function of organelles, which relies on specific changes in their protein composition. Of particular interest is the switch from heterotrophic to photoautotrophic seedling growth, for which cytoplasmic lipid droplets (LDs) play a critical role as depots for energy-rich storage lipids. Here, we present the results of a bottom-up proteomics study analyzing the total protein fractions and LD-enriched fractions in eight different developmental phases during silique (seed) development, seed germination, and seedling establishment in Arabidopsis ( Arabidopsis thaliana ). The quantitative analysis of the LD proteome using LD-enrichment factors led to the identification of six previously unidentified and comparably low-abundance LD proteins, each of which was confirmed by intracellular localization studies with fluorescent protein fusions. In addition to these advances in LD protein discovery and the potential insights provided to as yet unexplored aspects in plant LD functions, our data set allowed for a comparative analysis of the LD protein composition throughout the various developmental phases examined. Among the most notable of the alterations in the LD proteome were those during seedling establishment, indicating a switch in the physiological function(s) of LDs after greening of the cotyledons. This work highlights LDs as dynamic organelles with functions beyond lipid storage.